Application of MRI-guided hysteroscopic one-step resection in preserving the fertility of early endometrial cancer patients - Yu, Yi; Zhang, Lu; Sui, Long; Zhang, Hongwei; Chen, Limei (Frontiers in Oncology, 2025)
ObjectiveThis study aims to evaluate the role of MRI-guided hysteroscopic one-step precise resection in diagnosing suspected myometrial invasion (MI) of endometrial cancer (EC) in patients desiring fertility preservation and to analyze the impact of suspected MI on the outcomes of fertility-preserving treatments.MethodsA total of 169 patients with early-stage endometrial cancer who required fertility preservation were enrolled. Among them, 103 cases were ruled out for myometrial invasion by MRI (control group), while 66 cases exhibited suspected myometrial invasion. MRI-guided hysteroscopic one-step resection, which involved the removal of the endometrial lesion, the underlying basal layer, and 3–5 mm of myometrium, was performed for pathological examination. Patients with pathological exclusion of myometrial invasion received fertility-preserving treatment, and their clinical characteristics and treatment outcomes were compared with those of the control group.ResultsBased on the precise diagnosis of MRI-guided hysteroscopic one-step resection, 14 of the 66 patients with suspected myometrial invasion were confirmed by pathology and were included in the MI group for surgical treatment. The remaining 52 patients with no evidence of myometrial invasion were included in the non-MI group and received fertility-preserving treatment. The cumulative complete remission rate in the non-MI group was lower than that in the control group at 6 months (24.9% vs. 59.0%, P = 0.021) and 18 months (86.5% vs. 95.1%, P = 0.036). The cumulative recurrence rate in the non-MI group was higher than that in the control group after 12 months of follow-up (P = 0.037). There was no significant difference in the pregnancy rate between the non-MI group and the control group. There were three cases (25%) of successful pregnancy and full-term delivery in the non-MI group.ConclusionMRI-guided hysteroscopic one-step resection can accurately diagnose the presence of myometrial invasion in early endometrial cancer, which helps about 79% of patients preserve their fertility compared with MRI evaluation alone. Hysteroscopic resection of endometrial lesions, high-dose progesterone treatment, and follow-up are important for the successful fertility-preserving treatment of patients with early endometrial cancer.